The Smallholder Dairy Farmer Strategies to Address Feed Scarcity in Pangalengan, Indonesia - Firman, Achmad; Mauludin, Mochamad Ali; Salsabila, Khansa Nurul; Kusmayadi, Tendy (State Islamic University of Sultan Syarif Kasim Riau, 2025)
ABSTRACT. Livestock feed plays an important role in raising dairy cows. Good feed quality can improve the performance of milk production. In the situation of feed scarcity, dairy farmers provide feed with low nutritional value because of the difficulty in getting quality feed. Therefore, this study aims to explore the habits of dairy farmers in feeding their dairy cows and the strategies of dairy farmers to deal with feed scarcity. This research was conducted in Pangalengan district, from 2 to 30 September 2023 with 100 respondent farmers selected from 2 farmer groups (Cipanas and Los Cimaung). The study uses a mixed method (quantitative and qualitative methods) to find several findings related to feed availability in the context of feed scarcity. Interviews and focus group discussions are used to collect data and information from respondents and key persons in the cooperative (KPBS). The results showed that dairy farmers sought and found forages in their gardens, backyards, open access land (roadside and undeveloped plots), and others. Meanwhile, the cooperative guarantees the supply of concentrates for farmers in all seasons. The situation will be different in the dry season due to feed scarcity, especially for forages. Farmers have to spend money to buy forageswith or without collective action. The results also found that there were four strategies to anticipate forages scarcity, such as (1) forages preservation using silage technology, (2) reduction of forages and increasing concentrate, (3) utilization of agricultural waste, and (4) mixed strategies using strategies 2 and 3.